Association of Internet addiction with psychiatric symptom levels and sleep disorders: a systematic review and meta-analysis - Sun, Yuanlin; Wang, Zhen; Liu, Tianzhi (Frontiers in Psychology, 2025)
BackgroundMaladaptive Internet use is defined as Internet addiction disorders (IAD), which can lead to psychological problems and sleep disorders. Although many studies on the correlation between Internet addiction, psychiatric symptom levels, and sleep disorders have been conducted in recent years, there is no meta-analysis to substantiate the connection between these variables.MethodsWe systematically searched databases including Web of Science, PubMed, Embase, and the Cochrane Library to collect relevant studies using keywords associated with Internet addiction, psychological problems, and sleep disorders. All comparable studies that provided sufficient data (e.g., correlation coefficients) were included in our analysis.Results41 studies were included, and the results indicated that IAD was associated with psychological problems and sleep quality at moderate to low levels (depression: r = 0.39, 95%CI = 0.34–0.45; SMD = 1.34, 95%CI = 0.81–1.86; OR = 0.86, 95%CI = 0.46–1.26; anxiety: r = 0.30, 95%CI = 0.23–0.37; OR = 0.90, 95%CI = 0.29–1.52; stress: r = 0.34, 95%CI = 0.29–0.38; OR = 1.76, 95%CI = 0.37–3.16; sleep problems: r = 0.26, 95%CI = 0.19–0.33).ConclusionThis meta-analysis reveals that IAD is positively associated with depression, anxiety, and sleep problems, which indicates that individuals with IAD have an increased risk of depression, anxiety, and sleep problems. Hence, high attention should be paid to Internet addictive behaviors, and preventive and treatment measures should be adopted timely.Systematic review registrationThe publicly accessible registration record can be found at: https://www.crd.york.ac.uk/prospero/.